Developing knowledge networks: a practical methodology and experiences from cases. (21st February 2007) - Apostolou, Dimitris; Papailiou, Niki; Mentzas, Gregoris
This paper describes the role of Knowledge Networks (KNs) in modern organisations and presents a practical methodology for developing and fostering KNs. Experiences from real-life initiatives are used to illustrate the application of the methodology in organisations and to assess the impact of KNs on improving the management of organisational knowledge.